(untitled) (Journal of the Bangladesh Agricultural University, 2014)
An experiment was conducted at the Agronomy Field Laboratory of Bangladesh Agricultural University, Mymensingh to assess the effect of weeding on growth, yield and yield contributing characters of mungbean (Vigna radiata L.) cv. BINA mung- 4 during October 2011 to February 2012. The experiment was laid out in a randomized complete block design with four replications. The trial comprised seven treatments namely, T1 = no weeding, T2 = one-stage weeding (Emergence-Flowering), T3 = one-stage weeding (Flowering-Pod setting), T4 = one-stage weeding (Pod setting- Maturity), T5 = two-stage weeding (Emergence-Flowering and Flowering-Pod setting), T6 = two-stage weeding (Flowering-Pod setting and Pod setting-Maturity) and T7 = three-stage weeding (Emergence-Flowering and Flowering-Pod setting and Pod setting-Maturity). The growth parameters such as relative growth rate (0.075 g g-1 day- 1) and net assimilation rate (0.075 g m-2day-1) showed the best performance with T2 at one-stage weeding condition (Emergence-Flowering). Three-stage weeding ensured the highest plant height (58.62 cm) as well as the highest number of branches (4.45) and leaves (10.34) plant-1. Dry weight plant-1 (12.38g) was highest from three stage weeding and the lowest from no weeding treatment. The highest number of pods (22.03) plant-1, the longest pod (5.95 cm), the highest number of seeds (17.07) pod-1 and the highest seed yield (1.38 t ha-1) were obtained from three-stage weeding (Emergence-Flowering and Flowering-Pod setting and Pod setting-Maturity) in mungbean. On the other hand, the lowest seed yield was obtained under no weeding condition. The highest seed yield resulted in higher biological yield (4.70 t ha-1) and the highest harvest index (37.15%) in three-stage weeding and the lowest from no weeding. Number of pods plant-1, length of pod, number of seeds pod-1 and 1000-seed weight showed highly significant positive correlations with seed yield. These parameters strongly influenced the growth, yield and yield contributing characters of mungbean (Vigna radiata L.) DOI: http://dx.doi.org/10.3329/jbau.v11i1.18209 J. Bangladesh Agril. Univ. 11(1): 53-60, 2013